Economic Impact of CDM Implementation through Alternate Energy Resource Substitution - Sreekanth, K.J.; Jayaraj, S.; Sudarsan, N. (Center of Biomass & Renewable Energy, Diponegoro University, 2013)
Since the Kyoto protocol agreement, Clean Development Mechanism (CDM) hasgarnered large emphasis in terms of certified emission reductions (CER) not only amidst the globalcarbon market but also in India. This paper attempts to assess the impact of CDM towardssustainable development particularly in rural domestic utility sector that mainly includes lightingand cooking applications, with electricity as the source of energy. A detailed survey has undertakenin the state of Kerala, in southern part of India to study the rural domestic energy consumptionpattern. The data collected was analyzed that throws insight into the interrelationships of thevarious parameters that influence domestic utility sector pertaining to energy consumption byusing electricity as the source of energy. The interrelationships between the different parameterswere modeled that optimizes the contribution of electricity on domestic utility sector. The resultswere used to estimate the feasible extent of CO2 emission reduction through use of electricity as theenergy resources, vis-Ã -vis its economic viability through cost effectiveness. The analysis alsoprovides a platform for implementing CDM projects in the sector and related prospects withrespects to the Indian scenario.